2016
DOI: 10.1248/bpb.b15-00416
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol-Induced Disruption of the <i>Staphylococcus aureus</i> Cytoplasmic Membrane

Abstract: Farnesol, a sesquiterpene alcohol with an aliphatic carbon chain, inhibited the growth of Staphylococcus aureus and induced the leakage of potassium ions. We investigated the action of farnesol on the cytoplasmic membrane of S. aureus. No ion channels that would account for the loss of potassium ions were detected. Electron paramagnetic resonance measurements suggested that farnesol proceeds into the cytoplasmic membrane of S. aureus cells, where it induces the disordering and eventual disruption of the cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
(7 reference statements)
0
11
0
1
Order By: Relevance
“…We also demonstrated that at high concentrations, farnesol triggers a process of apoptosis in C. albicans and in human oral squamous carcinoma cells, which was preceded by ROS production in both eukaryotic cells (39)(40)(41). In S. aureus, several possibilities for farnesol's mechanism of killing have been proposed, including disruption of cell membrane integrity and leakage of K ϩ ions (38,(42)(43)(44). Therefore, given its toxicity, previous studies focused primarily on exploring the potential of exogenous farnesol as an antimicrobial agent.…”
Section: Figmentioning
confidence: 77%
“…We also demonstrated that at high concentrations, farnesol triggers a process of apoptosis in C. albicans and in human oral squamous carcinoma cells, which was preceded by ROS production in both eukaryotic cells (39)(40)(41). In S. aureus, several possibilities for farnesol's mechanism of killing have been proposed, including disruption of cell membrane integrity and leakage of K ϩ ions (38,(42)(43)(44). Therefore, given its toxicity, previous studies focused primarily on exploring the potential of exogenous farnesol as an antimicrobial agent.…”
Section: Figmentioning
confidence: 77%
“…N-(2-pyrimidyl) butylamine was confirmed to enhance the antibacterial effect of tobramycin, colistin, and ciprofloxacin on Pseudomonas aeruginosa [115]. Recent studies [116,117] have shown that both farnesol and hamamelitannin can reduce the virulence of Staphylococcus aureus and increase the sensitivity of Staphylococcus aureus to -lactam antibiotics. Synergistic effects of hamamelitannin, baicalin, hydrate, cinnamaldehyde, and antibiotics have been demonstrated in different infection models [118,119].…”
Section: Combinations Of Anti-qs Agents and Antibioticsmentioning
confidence: 97%
“…For example, HQNO was shown to increase S. aureus cell membrane fluidity, rendering S. aureus biofilms more susceptible to several membrane-targeting antibiotics and antiseptics, including chloroxylenol (88). Additionally, the C. albicans quorum sensing signal farnesol can disrupt the integrity of the S. aureus cell membrane (164,165), which, in turn, was hypothesized to contribute to farnesol's ability to shift S. aureus drug sensitivity profiles (164). It has been proposed that the hydrophobic character of both of these molecules may allow for their accumulation within the S. aureus membrane (88,164).…”
Section: Microbially Secreted Products Alter Antibiotic Tolerancementioning
confidence: 99%